Lower extremity osteoarthritis is associated with lower health-related quality of life among retired professional footballers. Issue 4 (2nd October 2018) - Gouttebarge, Vincent; Aoki, Haruhito; Kerkhoffs, Gino M. M. J.
ABSTRACT: Objective : The objective of the current study was to explore whether retired professional footballers suffering from lower extremity OA have a lower health-related quality of life than those without OA or current professional footballers. Methods : An observational study based on a cross-sectional design by means of questionnaires was conducted. Participants were retired and current professional footballers recruited by the World Players' Union (FIFPro). Information about lower extremity OA (clinically diagnosed by a medical professional) was gathered, while health-related quality of life (Global Physical Health and Global Mental Health scores) was assessed through a validated scale. Results : A total of 396 retired and 361 current professional footballers were included in the analyses (response rate of 54%). The group of retired professional footballers was on average 36 years old, and they had competed in professional football for 11 years (retired for 5 years). The group of current professional footballers was on average 25 years old, and they had been active in professional football for 7 years. Within the group of retired professional footballers, prevalence of lower extremity OA was 33%. Both Global Physical Health and Global Mental Health scores among retired professional footballers with lower extremity OA were significantly lower than among retired players without OA and current players, but these scores were nearly similar to the norm for the general population (regardless the presence of OA or not). Conclusions : Health-related quality of life among retired professional footballers with lower extremity OA was significantly lower than among retired players without OA and current players but nearly similar to the norm for the general population (regardless the presence of OA or not). A rational recommendation is that a support measure such as the After Career Consultation should be introduced among retired professional footballers in order to empower their sustainable health and quality of life, focussing especially on the prevention of the occurrence or worsening of lower extremity OA.